Apoptosis in the liver of male db/db mice during the development of obesity and type 2 diabetes - S. V. Michurina; I. Yu. Ishchenko; S. A. Arkhipov; M. A. Cherepanova; D. V. Vasendin; E. L. Zavjalov (Вавиловский журнал генетики и селекции)
Obesity and diabetes mellitus are known to lead to the development of metabolic syndrome and non-alcoholic fatty liver disease (NAFLD). The mechanisms of programmed cell death are actively involved in maintaining cellular homeostasis along development of NAFLD. Proteins of the BCL-2 family are key regulators of physiological and pathological apoptosis. Homozygous males of BKS.Cg-Dock7mLeprdb/+/+/J mice (db/db mice) are characterized by progressive obesity and the development of type 2 diabetes mellitus (DM2) with severe hyperglycemia at 4–8 weeks and organ lesions at 8–10 weeks of age. The aim of this research was to study the expression of molecular cell regulators of apoptosis in liver cells of db/db mice males at different stages of obesity and diabetes development (at the age of 10 and 18 weeks). Immunohistochemical analysis (using the indirect avidin-biotin peroxidase method) and morphometric evaluation of the expression of the antiapoptotic protein Bcl-2 and the proapoptotic protein Bad in liver cells of studied animals at different stages of obesity and DM2 were carried out. An excess of the value of the Bcl-2 protein staining area over the Bad protein staining area was revealed in the liver of 10-week-old animals. The Bcl-2/Bad expression area ratio in 10-week-old animals was twice as high as in 18-week-old animals, which indicates the presence of conditions for blocking apoptosis in the liver of younger db/db mice. At the 18th week of life, db/db mice displayed an almost threefold increase in the expression area of the Bad protein against the background of an unchanged expression of the Bcl-2 protein. The decrease in the Bcl-2/Bad staining area ratio in 18-week-old animals was due to the increase in the Bad expression area, which indicates the absence of antiapoptotic cell protection and creates conditions for activation of the mitochondrial pathway of apoptosis in the liver of male db/db mice with pronounced signs of obesity and DM2.